Conference attendees for the Business Woman's Club at San Jose State Teachers College - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Portrait of conference attendees for the Business Woman's Club at San Jose State Teachers College. Some of the attendees indicate the city or region they originate from with ribbons or small banners. Some of these localities include Illinois, Washington, Tennesse, and Seattle. The Tower and Quad of San Jose State Teachers College appears in the background.